Designing an integrated AHP based decision support system for supplier selection in automotive industry - Dweiri, Fikri; Kumar, Sameer; Khan, Sharfuddin Ahmed; Jain, Vipul (Expert systems with applications, 2016)
•AHP applied to decision making of automotive industry supplier selection.•Use of AHP in supplier selection gives decision maker confidence of consistency.•Sensitivity analysis to check the robustness of the supplier selection decision.•Proposed approach divides complex decision making into simpler hierarchy. The purpose of this paper is to propose a decision support model for supplier selection based on analytic hierarchy process (AHP) using a case of automotive industry in a developing country of Pakistan and further performs sensitivity analysis to check the robustness of the supplier selection decision. The model starts by identifying the main criteria (price, quality, delivery and service) using literature review and ranking the main criteria based on experts’ opinions using AHP. The second stage in the adopted methodology is the identification of sub criteria and ranking them on the basis of main criteria. Lastly perform sensitivity analysis to check the robustness of the decision using Expert Choiceۛ software. The suppliers are selected and ranked based on sub criteria. Sensitivity analysis suggests the effects of changes in the main criteria on the suppliers ranking. The use of AHP in the supplier selection gives the decision maker the confidence of the consistency and the robustness throughout the process. The AHP methodology adopted in this study provides managers in automotive industry in Pakistan with the insights of the various factors that need to be considered while selecting suppliers for their organizations. The selected approach also aids them in prioritizing the criterion. Managers can utilize the hierarchical structure of adopted supplier selection methodology suggested in this study to rank the suppliers on the basis of various factors/criteria. This study makes three novel contributions in supplier selection area. First, AHP is applied to automotive industry and use of AHP in the supplier selection gives decision maker the confidence of the consistency. Second, sensitivity analysis enables in understanding the effects of changes in the main criteria on the suppliers ranking and help decision maker to check the robustness throughout the process. Last, we find it important to come with a simple methodology for managers of automotive industry so that they can select the best suppliers. Moreover, this approach will also help managers in dividing the complex decision making problem into simpler hierarchy.